Genetic Variation of Leafhopper, Nephotettix virescens Distant Active Transmitters from Endemic and Non Endemic Areas of Rice Tungro Disease Based on RAPD Marker - Supriyadi .; Retno Wijayanti (Universitas Lampung, 2014)
ABSTRACTGenetic variation of leafhopper, Nephotettix virescens Distant active transmitters from endemic and non endemic areas of rice tungro disease based on RAPD marker. Leafhopper, Nephotettix virescens Distant (Hemiptera: Cicadellidae) plays an important role as a vector of rice tungro virus. However, the characters of N. virescens as a vector from endemic and non-endemic areas of tungro disease in Indonesia have not been well characterized and also available information is limited. The objective of this research was to study the character of N. virescens active transmitter from endemic and non-endemic of areas tungro disease based on RAPD markers. The N. virescens were collected from endemic area of Klaten (Central Java), Sleman (Yogyakarta) and non endemic area of Purwodadi (Central Java) Ngawi (East Java), and Pacitan (East Java). The N. virescens active transmitters were identified by their ability to transmit the virus based on Standard Evaluation System for Rice Tungro Virus, issued by IRRI. The genetic variations of N. virescens active transmitters were determined by using RAPD-PCR marker. Result of the research showed that three primers, OPB01, OPB10 and OPC08 amplified successfully of DNA template of N. virescens through RAPD-PCR technique. Based on the dendrogram, there were initial facts of possible genetic differences between the populations of N. virescens from endemic and non endemic areas of rice tungro disease. The N. virescens from endemic area of Klaten and Sleman are similar genetically but different from the N. virescens non endemic of Purwodadi, Pacitan and Ngawi.